Uwagi na temat wzornictwa przemysłowego w Polsce w latach 70. - Wybieralski, Wojciech (Człowiek i Społeczeństwo, 2017)
Wojciech Wybieralski, Uwagi na temat wzornictwa przemysłowego w Polsce w latach 70. [Comments on Industrial Design in Poland in the 1970s], edited by W. Bryl-Roman, „Człowiek i Społeczeństwo” vol. XLIII: Projektowanie w latach 70. [Designing in the 1970s], Poznań 2017, pp. 13-30, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271. The paper discusses issues concerning the Polish industrial design of the‘70s in regard to social and economical situation of a country belonging by the time to the ‘Eastern Bloc’. The author argues the design industry had been strictly dependent on the social and political matters of that time. His judgement results not only from the review and analysis of the accessible information but most of all from his personal experiences of participation in several design teams operating in Polish industry of that time. The emphasis is laid on the specific area of design which is performed in various branches and capacities that produces objects of everyday use, machines, appliances and other constituents of human ambience. The author remarks also the organisational and legal issues of the profession and the design education in academies by the time. Industrial design, in his opinion, was strictly connected with visual arts, different technical disciplines, humanities and social sciences. The most distinctive features of design are its multidisciplinarity, the activity in the realms of usability and the formal (visual and aesthetic) matters. The profession balances questions of function, form, technology and economy. Even though the ‘70s as many other periods in Polish politics and economy did not result in expected successes, the discipline of design managed to survive the severe time of the 80s and create the base for operating in the market economy after the 1989.